2015
DOI: 10.1182/blood-2014-07-591461
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of myeloid malignancies with inv(3)/t(3;3) reveals a predominant involvement of RAS/RTK signaling pathways

Abstract: Key Points• inv(3)/t(3;3) disease exhibits high rates of activated RAS/ RTK signaling, epigenetic modifier, splice, and transcription factor mutations.• AML and MDS with inv(3)/t(3;3) display similar mutational and gene expression profiles and should be considered a single molecular entity.Myeloid malignancies bearing chromosomal inv(3)/t(3;3) abnormalities are among the most therapy-resistant leukemias. Deregulated expression of EVI1 is the molecular hallmark of this disease; however, the genome-wide spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 52 publications
10
67
1
2
Order By: Relevance
“…Two patients harbored the same SMC1A variant R96H, previously reported in AML. 33 We found a hotspot in SMC3 because 3 of 5 mutations involved the codon R661 in the hinge domain of the protein.…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Two patients harbored the same SMC1A variant R96H, previously reported in AML. 33 We found a hotspot in SMC3 because 3 of 5 mutations involved the codon R661 in the hinge domain of the protein.…”
Section: Gene Mutationsmentioning
confidence: 99%
“…25 A recent study demonstrated that mutations activating RAS/receptor tyrosine kinase pathway are coupled with EVI1 overexpression in 98% of inv(3)/t(3;3) cases and contribute to leukemic transformation. 26 Although studies have shown that 3q26.2 abnormalities in AML are associated with an unfavorable prognosis, the role of 3q26.2 in CML is largely unknown. Only occasional single-case reports and small case series composed of few cases are available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They further showed that although alterations of KRAS, NF1, and RUNX1 were more frequent in AML than MDS, the differences were not statistically significant. 16 By using next-generation sequencing, including whole-transcriptome and whole-exome sequencing, Gröschel and associates 21 have showed that mutations in genes activating RAS/ receptor tyrosine kinase occur in 98% of myeloid neoplasms with inv(3)/t(3;3), and these mutations were mainly present in the dominant ectopic viral integration site 1 (EVI1)-rearranged clone. These authors further demonstrated the strong homogeneity between inv(3)/t(3;3)-harboring AML and MDS based on gene expression profiling and the pattern of cooperating genetic lesions using cluster and principal component analyses.…”
mentioning
confidence: 99%